Bioactive food components in the diet of patients diagnosed with cancer - Klekot, Konrad; Zubelewicz-Szkodzińska, Barbara (European Journal of Clinical and Experimental Medicine, 2017)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Cancer, after cardiovascular disease, is the second most common cause of death both in Poland and Europe, so it is important to investigate and search for dietary components with anti-cancer properties. Components which can modulate different stages of carcinogenesis through epigenetic process are called bioactive food components. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of this study was to evaluate nutritional habits of patients diagnosed with cancer in terms of level of bioactive food components consumption. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A group of 123 patients diagnosed with cancer were enrolled the study. The study was conducted by means of an anonymous questionnaire on diet history prepared by the authors. Statistical analysis was performed using IBM SPSS software, statistical significance was adopted at the level of p < 0.05. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Based on the results of the questionnaires, major risk factors that increase the prevalence of cancer disease were age (above 55 years) and increased BMI (the score indicated overweight or obesity). Additionally, it was observed that cancer diagnosis resulted in change of eating habits in approx. 61.8% of the participants. Enrolled patients mostly consumed inadequate amounts of green vegetables, legumes, green tea and whole grains before the diagnosis. Moreover, patients with breast and colorectal cancer were found to be more likely to consume more red meat in comparison to others. – Both non-modifiable factors: age and modifiable ones: body weight and lifestyle influence morbidity. – Most participants ate incorrectly before cancer diagnosis; diagnosis of the disease changed their eating habits.